Ragam Kohesi Leksikal Pada Rubrik Pembaca Menulis Koran Jawa Pos - Pitoyo, Andri (Universitas Nusantara PGRI Kediri, 2021)
This study emphasizes the usage description of (1) lexical cohesion in the form of repetitions in the Pembaca Menulis rubric of Jawa Pos newspapers, (2) lexical cohesion in the form of synonyms in the Pembaca Menulis rubric of Jawa Pos newspapers, and (3) lexical cohesion in the form of antonyms in the Pembaca Menulis rubric of Jawa Pos newspapers. Newspapers are source of written news that can be read at any time. In addition to presenting news that is happening around the community, newspapers are also place to express aspirations, one of which is the Pembaca Menulis rubric of Jawa Pos newspapers from May and June 2020 editions. A good and complete text requires cohesive sentences both grammatically and lexically. The data source of this research is the Jawa Pos newspapers from May and June 2020 editions which are taken randomly. This research is a qualitative research that uses a critical text analysis approach. The results of the study show that there are repetitions, synonyms, and antonyms in the May and June 2020 editions of Pembaca Menulis rubric of Jawa Pos Newspapers.